AKUISISI DATA MEDIA SOSIAL PEMERINTAH UNTUK MENGANALISIS KETERBUKAAN INFORMASI PENYEBARAN COVID-19 - Nina Fadilah Najwa; Muhammad Ariful Furqon; Endah Septa Sintiya; Ari Cahaya Puspitaningrum (Jurnal Sosioteknologi, 2021)
The Covid-19 pandemic is spreading rapidly throughout the world, including in Indonesia. Every province in Indonesia has been using social media to share Covid-19 information. This study aims to see the activeness and openness of provincial governments’ social media about Covid-19 information. The steps taken were crawling data on governments’ social media, namely Instagram by taking 300 posts. Then, data extraction was carried out to filter data related to Covid 19. This study also conducted a comparison or ranking of provinces that have had Covid-19 confirmed cases. The results show that DKI Jakarta Province is the area that has the most Covid-19 confirmed patients. Meanwhile, the most active social media is North Sumatra Province. There is an influence on the growth rate of confirmed cases of Covid-19 with the active provincial government social media. The research contribution has provided the analysis results of data acquisition and is used as knowledge for government officials to increase the social media activeness of their local government.